Transformation of Down Payment in Sharia Financing in Indonesia Based on Buying and Selling ‘Urbūn and Ḥāmish Jiddiyyah - Hasanudin Hasanudin (Universitas Islam Negeri Jakarta, 2023)
Down payment is commonly practiced in society. Islamic law recognizes the concepts of ‘urbūn and ḥāmish jiddiyyah, which have a similar meaning to a down payment. However, the concepts of customary law and Islamic law are somewhat different. There are differences in ulama’s opinions concerning the permissibility of a down payment. This article aims to analyse the correlation between the concepts of down payment, ‘urbūn, ḥāmish jiddiyyah, and the legal status of a down payment in Islamic law. Using a normative legal approach, this topic is is examined by considering the uṣūl al-fiqh-based views of the classical and contemporary ulama. This study shows that scholarly debate about down payments starts from the ownership status of the money and the impact when the sale and purchase are canceled. Besides, the aspect of its prohibition and benefit are intertwined. Contemporary fatwas allow the practice of down payment with the consideration of modern needs and maṣlaḥah. This finding implies that down payment will become more widespread among the public and the Islamic finance sector. Therefore, A monitoring scheme is needed to avoid the violation of sharia in down payment implementation. Abstrak: Uang panjer lumrah dipraktikkan di masyarakat. Hukum Islam mengenal konsep ‘urbūn dan ḥāmish jiddiyyah yang memiliki kemiripan makna dengan uang panjer. Namun konsep hukum adat dan hukum Islam tersebut tidak seluruhnya sama. Ada perbedaan dan status hukumnya pun berbeda di kalangan ulama. Artikel ini bertujuan menganalisis korelasi konsep uang panjer dan ‘urbūn dan ḥāmish jiddiyyah dan status hukum uang panjer dalam perspektif hukum Islam. Dengan metode pendekatan hukum normatif, tema ini dikaji dengan mempertimbangkan pandangan fikih yang dicetuskan ulama masa lalu dan kontemporer serta mempertimbangkan pertimbang ushul fikih. Hasilnya, perdebatan ulama tentang uang panjer berawal dari status kepemilikan uang tersebut dan dampaknya ketika jual beli batal dilakukan. Di sisi lain, sisi keharaman dan kemaslahatan saling berkelindan. Fatwa kontemporer mengambil pendapat boleh dengan pertimbangan kemaslahatan dan kebutuhan modern. Implikasi dari temuan ini, penggunaan uang panjer akan semakin luas di kalangan masyarakat dan sektor keuangan syariah. Diperlukan skema pengawasan agar praktik uang panjer tersebut tidak melanggar ketentuan syariah.